PENDIDIKAN TOLERANSI DALAM PEMBENTUKAN SIKAP SANTRI - Ari Pratama Putra; Sapiudin (Qiro'ah : Jurnal Pendidikan Agama Islam, 2024)
Tolerance-based education is important to implement in Islamic boarding schools to build an attitude of tolerance for students. Moral degradation, fighting between students, insulting each other, insulting each other, spreading slander and intolerance are indicators of the failure of an educational institution. Tolerance education is a solution for building human character who can respect and respect differences. Radicalism and Intolerance are psychological diseases that are very dangerous for humans, because this disease resides in the human heart and human mindset, so to cure this disease is contained in the perspective of Islamic education which studies it in conferences, especially in Islamic boarding school institutions. In this research, the method used is a qualitative method with a research study approach at the Al-Karimiyah Islamic Boarding School, Depok. The results of this research state that Islamic education which is full of tolerance values ​​contributes to overcoming the problem of intolerance. Islamic education has a very urgent role in describing the motives for religious violence carried out by a group of people who carry out violence in the name of religion. Islamic education also functions to explain how someone becomes radical, Islamic education even provides a solution for radical people to no longer be involved in radicalism and intolerance through Islamic boarding school-based tolerance education.